Development Of Mining Safety Program For Pt Putra Perkasa Abadi Based On Safety Culture Maturity Assessment - Hamdan, Alifal; Elok Larasati, Hanum; Ridwan Lindrianto, Ardhiansyah (Sean Institute, 2023)
Accidents and disasters can be caused by cultural and safety factors, as suggested by Barry Turner in his pioneering work 'Man-Made Disasters.' The implementation of safety culture is one of the crucial aspects that should be applied, especially in the workplace safety. The term safety culture began to be widely used since the Chernobyl nuclear disaster in 1986, and interest in safety culture has continued to grow, including in Indonesia. This explanation is supported by the issuance of the Director General of Mineral and Coal Decision Number 10.K/MB.01/DJB.T/2023 (Kepdirjen Minerba 10 Year 2023) concerning Technical Guidelines for the Assessment of Mining Safety Performance, which is one of the tools to measure the maturity level of safety culture. Through Kepdirjen Minerba 10 Year 2023, the measurement of safety culture is more focused on companies engaged in the mining sector. Therefore, PT Putra Perkasa Abadi site PT Bukit Asam Tbk (PPA-BA) uses Kepdirjen Minerba 10 Year 2023 to measure the level of safety culture in Semester 2 in 2023. This measurement aims not only to assess the level of safety culture maturity within the company but also serves as a basis for developing the mining safety program in 2024. The measurement uses data collection methods such as documentation review, questionnaires, interviews, observations, focus group discussions, testing, and data analysis. The results of data collection are then averaged for each indicator and added up to obtain the safety culture maturity level. Based on the analysis, it is known that the safety culture maturity level at PPA-BA is 0.56, indicating a reactive position. The results of this assessment are used as one of the foundations for the development of the mining safety program. Previously, the development of the mining safety program only considered legal regulations.